The menstrual cycle and anterior cruciate ligament injury risk: Implications of menstrual cycle variability - Vescovi, J. D. (Sports Medicine, 2011)
The menstrual cycle and associated hormonal fluctuations are considered risk factors for non-contact anterior cruciate ligament (ACL) injuries in female athletes. Researchers have used a `normal` 28-day cycle and relied upon menstrual history questionnaires or a biological sample (i.e. blood, saliva) taken on a single day to identify the phase of the menstrual cycle where an ACL tear has occurred. However, evidence from available studies lack adequate consideration of menstrual cycle variability that exists in the general population and neglect to acknowledge the greater prevalence of subtle menstrual disturbances in physically active and athletic women. Inter- and intra-woman menstrual cycle variability is large for total cycle, follicular phase and luteal phase length ranging from 22 to 36, 9 to 23 and 8 to 17 days, respectively (95% CI). More importantly, subtle menstrual disturbances such as anovulation and luteal phase defects are common in athletic women with a high prevalence of cycle-to-cycle variations. To complicate matters further, menstrual history questionnaires inaccurately quantify cycle length compared with prospective monitoring of cycle length, highlighting the need to implement more sophisticated methods for identifying menstrual cycle/phase characteristics. Regardless of variability and/or the presence of subtle menstrual disturbances, women may still have regularly occurring menses, making it extremely difficult to accurately identify the phase of the menstrual cycle where an ACL tear has occurred based on a menstrual history questionnaire or a single biological sample. Therefore, the assumption that normal ovarian endocrine function is synonymous with regularly occurring menses in physically active and athletic women is unjustified. Thus, definitive conclusions are not warranted regarding the association between the menstrual cycle and non-contact ACL injury risk based on currently available data. Future work in this area must incorporate methods to prospectively evaluate and accurately characterize menstrual cycle characteristics if we are to link the hormonal fluctuations of the menstrual cycle to non-contact ACL injury risk.